Nasionalisme Simbolik dalam Puisi Aḥinnu ilá Khubzi Ummī Karya Mahmoud Darwish: Studi Stilistika - Semiotika Riffaterre - Adi Reksa, Muhamad Fahri; Supriadi, Rinaldi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
The poem Aḥinnu ilá Khubzi Ummī by Mahmoud Darwish displays a personal longing for mother and home which at the same time implies national consciousness and Palestinian resistance. This personal experience is constructed through everyday symbols such as bread, coffee and prayer which form symbolic nationalism. This research aims to reveal how the symbolic structure of poetry moves meaning from the personal realm to collective symbols of struggle and national identity, with a focus on the transformation of meaning through poetic language. The research uses a qualitative-descriptive approach to literature with content analysis. Primary data is the text of the poem Aḥinnu ilá Khubzi Ummī, while secondary data comes from journals, books and previous studies related to Darwish poetry, stylistics and semiotics. The analysis integrates stylistics to examine diction, imagery, metaphors and symbols, as well as Riffaterre's semiotics through heuristic and hermeneutic stages to reveal the indirect meaning that forms symbolic nationalism. Aḥinnu ilá Khubzi Ummī's poetry forms symbolic nationalism through the transformation of meaning from personal experience to collective experience. Riffaterre's stylistic and semiotic analysis shows that diction, imagery, metaphors and domestic symbols such as bread, coffee, mother's touch and religious expressions move from literal to symbolic meanings that emphasize the cultural identity, collective memory and spirit of resistance of the Palestinian people. This poem emphasizes the function of poetic language as a medium for expression of national identity and symbolic struggle, while also emphasizing the relevance of the integration of stylistics and semiotics in revealing indirect meaning in modern Arabic literary works